Bioactive Components of Myracrodruon urundeuva against SARS-CoV-2: A Computational Study - Sabrina Kelly Silva Alves; Cássio Silva Sousa; Edilanne Katrine Amparo Viana; Hellen Cris Araújo Souza; Maycon Douglas Araújo Souza; Arthur Serejo Neves Ribeiro; Vanessa de Sousa do Vale; Muhammad Torequl Islam; Joabe Lima Araújo; Jefferson Almeida Rocha (MDPI AG, 2023)
SARS-CoV-2 (severe acute respiratory distress syndrome coronavirus 2) is the causative agent for the novel coronavirus disease 2019 (COVID-19). It raises serious biosecurity questions due to its high contagious potential, thereby triggering rapid and efficient responses by the scientific community to take necessary actions against viral infections. Cumulative scientific evidence suggests that natural products remain one of the main sources for pharmaceutical consumption. It is due to their wide chemical diversity that they are able to fight against almost all kinds of diseases and disorders in humans and other animals. Knowing the overall facts, this study was carried out to investigate the chemical interactions between the active constituents of a promising medicinal plant, Myracrodruon urundeuva, and some specific proteins of SARS-CoV-2. For this, we used molecular docking to predict the most appropriate orientation by binding a molecule (a ligand) to its receptor (a protein). The best results were evaluated by screening their pharmacokinetic properties using the online tool pkCSM. Findings suggest that among 44 chemical compounds of M. urundeuva, agathisflavone, which is abundantly present in its leaf, exhibited excellent molecular affinity (−9.3 to −9.7 kcal.mol−1) with three functional proteins, namely, Spike, MPro, and RBD of SARS-CoV-2. In conclusion, M. urundeuva might be a good source of antiviral agents. Further studies are required to elucidate the exact mechanism of action of the bioactive compounds of M. urundeuva acting against SARS-CoV-2.